Reduction of Regional Economic Disparities Through the ASEAN Economic Community Framework - Baby Azzura; Irnes Febrinabila; Naia Khusnul Nabila; Radhwa Zahirah; Salsabila Salsabila (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Regional economic integration through the ASEAN Economic Community (AEC) framework, established in 2015, aims to create a single market and production base while promoting equitable development and reducing poverty across Southeast Asia. However, economic disparities remain a persistent structural challenge within the region. This study examines the multi-dimensional facets of inequality among ASEAN member states encompassing severe gaps in income, infrastructure connectivity, and digital literacy and analyzes them through the lens of Fernando Henrique Cardoso’s dependency theory. The data reveals profound disparities, highlighted by a stark 77:1 ratio in per capita GDP between Singapore and Myanmar , alongside a severe digital divide where internet penetration in CLMV countries (Cambodia, Laos, Myanmar, and Vietnam) remains below 50%. Although mechanisms like the Initiative for ASEAN Integration (IAI) offer technical assistance and capacity building , their efficacy is limited by low institutional absorption and financial volatility. Under current conditions, the AEC risks inducing a state of